PHARMACEUTICAL AUDIT PROCESS, OUTCOMES, AND IMPLICATIONS–OVERVIEW - R. K., KRUTHIKA; MISHRA, SANGITHA; M., ARJUN; VENKATESH, M. P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
The audit process is a crucial component of regulatory compliance and quality assurance in both the United States of America (USA) and the European Union (EU). This review paper compares and analyses the audit processes, results, and ramifications in these two important markets. The study investigates how pharmaceutical audits affect patients’ trust, market stability, and profitability of a company while highlighting the need for adherence to quality standards. Data integrity, supply chain complexity, and adherence to exacting quality standards are just a few of the notable difficulties faced by auditors in the USA and EU. There is a need to have a strong pharmacovigilance system as well to guarantee the security and effectiveness of pharmaceutical products for patients. This study can be useful reference material for stakeholders, decision-makers, and companies looking to increase accountability, reduce risks, and uphold the integrity of a firm’s operations in the global market. A thorough analysis of audit procedures in the USA and EU will facilitate in promotion of effective and efficient manufacturing, control, and distribution of pharmaceutical products while boosting confidence among patients and in the healthcare system as a whole.